A novel mechanism and treatment target for presynaptic abnormalities in specific striatal regions in schizophrenia - Barakauskas, Vilte E; Beasley, Clare L; Barr, Alasdair M; Ypsilanti, Athena R; Li, Hong-Ying; Thornton, Allen E; Wong, Hubert; Rosokilja, Gorazd; Mann, J John; Mancevski, Branislav; Jakjovski, Zlatko; Davcheva, Natasha; et al. (Springer Science and Business Media LLC, 2010)
Abnormalities of amount and function of presynaptic terminals may have an important role in the mechanism of illness in schizophrenia. The SNARE proteins (SNAP-25, syntaxin, and VAMP) are enriched in presynaptic terminals, where they interact to form a functional complex to facilitate vesicle fusion. SNARE protein amounts are altered in the cortical regions in schizophrenia, but studies of protein-protein interactions are limited. We extended these investigations to the striatal regions (such as the nucleus accumbens, ventromedial caudate (VMC), and dorsal caudate) relevant to disease symptoms. In addition to measuring SNARE protein levels, we studied SNARE protein-protein interactions using a novel ELISA method. The possible effect of antipsychotic treatment was investigated in parallel in the striatum of rodents that were administered haloperidol and clozapine. In schizophrenia samples, compared with controls, SNAP-25 was 32% lower (P=0.015) and syntaxin was 26% lower (P=0.006) in the VMC. In contrast, in the same region, SNARE protein-protein interactions were higher in schizophrenia (P=0.008). Confocal microscopy of schizophrenia and control VMC showed qualitatively similar SNARE protein immunostaining. Haloperidol treatment of rats increased levels of SNAP-25 (mean 24%, P=0.003), syntaxin (mean 18%, P=0.010), and VAMP (mean 16%, P=0.001), whereas clozapine increased only the VAMP level (mean 13%, P=0.004). Neither drug altered SNARE protein-protein interactions. These results indicate abnormalities of amount and interactions of proteins directly related to presynaptic function in the VMC in schizophrenia. SNARE proteins and their interactions may be a novel target for the development of therapeutics.